Detecting respiratory impairment in newly diagnosed rheumatoid arthritis by MRC dyspnoea scale and microfibrillar-associated protein 4 - Bjørk K. Sofiudottir; Sören Möller; Robin Christensen; Stefan Harders; Grith L. Sørensen; Jesper Blegvad; Mette Herly; Dzenan Masic; Grazina Urbonaviciene; Frank Andersen; Christin Isaksen; Brian Bridal Løgstrup; et al. (European Clinical Respiratory Journal)
Objectives To evaluate the Medical Research Council (MRC) dyspnoea scale and serum Microfibrillar-associated protein 4 (MFAP4) levels for the detection of respiratory impairment in newly diagnosed rheumatoid arthritis (RA).Methods Patients underwent blood tests, pulmonary function tests (PFT) and dyspnoea assessment using the MRC scale. Respiratory impairment was defined as a diffusion capacity of the lungs for carbon monoxide (DLCO) <80% predicted or FEV1/FVC <70%. The primary outcomes were the MRC and MFAP4’s sensitivity, specificity, and diagnostic odds ratio (DOR) with 95% confidence intervals (CI).Results One hundred and thirty-one patients had available baseline tests. Mean age was 57.7 years (SD: 10.9), 61% were female, and 45% had respiratory impairment. For MRC score ≥ 2, the sensitivity was 39.0% (95% CI 26.5; 52.6), specificity 76.4% (95% CI 64.9; 85.6), and DOR 2.07 (95% CI 0.97; 4.40). For MFAP4 > 29.0 U/mL, the sensitivity was 62.7% (95% CI 49.1; 75.0), specificity 56.9% (95% CI 44.7; 68.6), and DOR 2.22 (95% CI 1.10; 4.50). The DOR was 3.01 (95% CI 1.27; 7.16) for MFAP4 detecting respiratory impairment when adjusted for age, sex and smoking status.Conclusion The MRC dyspnoea score and unadjusted MFAP4 levels were poor predictors of respiratory impairment in patients with early treatment-naïve rheumatoid arthritis.